Prevalence and predictors of storage lower urinary tract symptoms in perimenopausal and postmenopausal women attending a menopause clinic. Issue 10 (October 2015) - Terauchi, Masakazu; Hirose, Asuka; Akiyoshi, Mihoko; Owa, Yoko; Kato, Kiyoko; Kubota, Toshiro
Abstract Objective: This study was undertaken to evaluate the prevalence and predictors of storage lower urinary tract symptoms (LUTS) in perimenopausal and postmenopausal women attending a menopause clinic. Methods: The records of 351 women aged 40 to 76 years who enrolled in a health and nutrition education program at a menopause clinic were analyzed cross-sectionally. The prevalence of frequency, nocturia, urge incontinence, and stress incontinence was estimated based on women's responses to the Menopausal Health-Related Quality of Life Questionnaire. Effects of background characteristics, including age, menopause status, vaginal dryness, body composition, cardiovascular parameters, physical fitness, and psychological symptoms, on storage LUTS were assessed using multivariate logistic regression analysis. Results: Frequency, nocturia, urge incontinence, and stress incontinence were reported by 45.9%, 10.8%, 11.4%, and 32.8% of women, respectively. Multiple logistic regression analysis revealed independent associations between storage LUTS and the following predictors after adjustment: frequency was associated with nonrestorative sleep score (odds ratio, 1.63; 95% CI, 1.35-1.95); nocturia was associated with nonrestorative sleep score (odds ratio, 2.26; 95% CI, 1.57-3.25) and waist-to-hip ratio (odds ratio, 1.12; 95% CI, 1.05-1.18); urge incontinence was associated with reaction time (odds ratio, 1.10; 95% CI, 1.01-1.19); and stress incontinence was associated with body fat (odds ratio, 1.06; 95% CI, 1.03-1.09). Conclusions: Storage LUTS are highly prevalent in perimenopausal and postmenopausal women attending a menopause clinic. Nonrestorative sleep score is associated with frequency and nocturia; body fat and visceral fat accumulation are associated with nocturia and stress incontinence; and delayed reaction time is associated with urge incontinence. Careful evaluation of nonrestorative sleep, body fat and visceral fat accumulation, or delayed reaction time might reveal undisclosed storage LUTS in this population.